The relationship between superstitious behavior and the conditioned reinforcing stimulus: a systematic replication of Lee (1996). (Brazilian Journal of Behavioral and Cognitive Therapy, 2010)
This study was conducted in order to ascertain if a conditioned reinforcing stimulus can give rise to superstitious behavior, using a systematic replication of Lee (1996). The task of the 12 participants was to change the icon display on the left side of the computer screen by clicking the mouse button. Icon changes did not depend on cursor location, but rather on the number of clicks. During phase 1, the icon display changed according to a variable ratio schedule, in which the first four changes referred to changes in the icon display only and the fifth change referred to an icon match. During phase 2, following a number of mouse clicks where icon change was not observed, the next four clicks changed the icon arrangement, although the icons remained the same, and the fifth click produced an icon match. In phase 3, icon match occurred immediately after "n" clicks. Two types of superstitious responses were identified: (1) clicking the mouse button on icons or in any other place on the screen that did not have icons and (2) location changes after an absence of change or following icon changes.
Keywords: Superstitious behavior; Conditioned reinforcing stimulus; Response-independent environmental changes